Rh(I)-Catalyzed Carbon–Carbon Double-Bond Formation by Coupling of (Quinolin-8-yl)methanone with Arylaldehyde Tosylhydrazone - Zhang, Yexia; Wang, Jingjing; Wang, Jianhui (Synlett, 2013)
An alternative method for the direct arylvinylation of (quinolin-8-yl)methanone with substituted N′-benzylidene-4-methylbenzenesulfonohydrazide is described. The desired 3-aryl-1-(quinolin-8-yl)prop-2-en-1-one products are obtained in high yields through the catalytic reaction of (quinolin-8-yl)methanone and N′-arylidene-4-methylbenzenesulfonohydrazide (2 equiv) with [Rh(PPh3)3Cl] (10 mol%), Ag2O (0.5 equiv), and Cs2CO3 (2 equiv) at 130 °C for 48 hours. Two plausible mechanisms involving C–H activation and migratory insertion of the carbene into the rhodium–carbon bond were proposed to explain the formation of the product.
Keywords: quinolinone; rhodium complex; hydrazones; C–C coupling; double-bond formation